2018
DOI: 10.1038/s41612-018-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of CMIP5 multi-model mean in assessing Indian monsoon simulations

Abstract: Considering the wide use of the multi-model mean (MMM) on the seasonal time scale, this work examines its fidelity in simulating some important characteristics of the Indian summer monsoon using Coupled Model Intercomparison Project Phase 5 (CMIP5) simulations. It is noted that the MMM captures the observed spatial pattern and annual cycle of surface air temperature to a great extent, but there are large biases in magnitude, particularly over north India. For precipitation, only the broad-scale features are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 13 publications
(12 reference statements)
2
23
1
Order By: Relevance
“…Among the main biases is an underestimation of precipitation by 2 to 6 mm/day over some central regions of India (Figure c). This problem is however common to many global and regional models over the Indian subcontinent, and in fact, our model performance is in line with most previous studies (Mishra et al, ; Singh et al, ; Sperber et al, ). This dry bias may be associated with reduced soil moisture availability simulated by CLM4.5 (Maharana et al, ).…”
Section: Resultssupporting
confidence: 91%
“…Among the main biases is an underestimation of precipitation by 2 to 6 mm/day over some central regions of India (Figure c). This problem is however common to many global and regional models over the Indian subcontinent, and in fact, our model performance is in line with most previous studies (Mishra et al, ; Singh et al, ; Sperber et al, ). This dry bias may be associated with reduced soil moisture availability simulated by CLM4.5 (Maharana et al, ).…”
Section: Resultssupporting
confidence: 91%
“…According to CESM-LENS, in spite of seemingly stable SPEI projections due to moderate increases in future monsoon rainfall, the long-lived rise in surface-air temperatures will conspire with El Niño to yield extreme seasonal heat and dryness. Since our analysis is based on the single model (CESM-LENS), additional analyses with other global climate models that show reasonable skill in capturing the ENSO-monsoon relationship 41,42 can provide additional insights into the increasing contribution of El-Nino events in driving the rising concurrence of hot and dry extremes over India under the warming climate. Nonetheless, the increased severity of hot and dry monsoon extremes is likely to pose a substantial challenge to the future food security of the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Ashfaq et al, 2017;Jain et al, 2019;Mishra, Sahany, et al, 2018;Sabeerali et al, 2015;Saha et al, 2014) based on the CMIP5-GCMs reported that the majority of GCMs fail to capture the summer monsoon variability over South Asia. Consistent with the CMIP5-GCMs, we find that the majority of the CMIP6-GCMs are not able to capture the South Asian summer monsoon variability (Table S3 and Figures 3 and S4).…”
Section: Discussionmentioning
confidence: 99%